Effects of complement gene‐set polygenic risk score on brain volume and cortical measures in patients with psychotic disorders and healthy controls. Issue 8 (12th September 2020) - Holland, Jessica F.; Cosgrove, Donna; Whitton, Laura; Harold, Denise; Corvin, Aiden; Gill, Michael; Mothersill, David O.; Morris, Derek W.; Donohoe, Gary
Abstract: Multiple genome‐wide association studies of schizophrenia have reported associations between genetic variants within the MHC region and disease risk, an association that has been partially accounted for by alleles of the complement component 4 (C4) gene. Following on previous findings of association between both C4 and other complement‐related variants and memory function, we tested the hypothesis that polygenic scores calculated based on identified schizophrenia risk alleles within the "complement" system would be broadly associated with memory function and associated brain structure. We tested this using a polygenic risk score (PRS) calculated for complement genes, but excluding C4 variants. Higher complement‐based PRS scores were observed to be associated with lower memory scores for the sample as a whole ( N = 620, F change = 8.25; p = .004). A significant association between higher PRS and lower hippocampal volume was also observed ( N = 216, R 2 change = 0.016, p = .015). However, after correcting for further testing of association with the more general indices of cortical thickness, surface area or total brain volume, none of which were associated with complement, the association with hippocampal volume became non‐significant. A post‐hoc analysis of hippocampal subfields suggested an association between complement PRS and several hippocampal subfields, findings that appeared to be particularly driven by the patient sample. In conclusion, our study yielded suggestive evidence of association between complement‐based schizophrenia PRS and variation in memory function and hippocampal volume.